2021
DOI: 10.3390/ph14030233
|View full text |Cite
|
Sign up to set email alerts
|

How to Treat Hepatocellular Carcinoma in Elderly Patients

Abstract: Hepatocellular carcinoma (HCC) is the primary tumour of the liver with the greatest incidence, particularly in the elderly. Additionally, improvements in the treatments for chronic liver diseases have increased the number of elderly patients who might be affected by HCC. Little evidence exists regarding HCC in old patients, and the elderly are still underrepresented and undertreated in clinical trials. In fact, this population represents a complex subgroup of patients who are hard to manage, especially due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 143 publications
0
16
0
Order By: Relevance
“…Surgical outcomes in elderly patients undergoing liver resection are well‐studied in the literature 13‐18 . Cho et al concluded that liver resection could be performed safely in patients aged ≥70 years as in younger patients 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical outcomes in elderly patients undergoing liver resection are well‐studied in the literature 13‐18 . Cho et al concluded that liver resection could be performed safely in patients aged ≥70 years as in younger patients 19 .…”
Section: Discussionmentioning
confidence: 99%
“…It is challenging to estimate the risk‐benefit ratio of various treatment options in the elderly population, which has a limited life expectancy and a reduced ability to adapt to physical and psychological stress. This evaluation could be difficult; therefore, we recommend the use of standard performance status scales, which are used daily in clinical practice (such as Karnofsky performance status or Eastern Cooperative Oncology Group performance status) to evaluate surgical candidacy in these patients 14 . Frailty is another parameter that is being extensively utilized in the surgical literature 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis, published in 2019, showed no significant difference in terms of blood loss, transfusions, liver failure, Clavien-Dindo III/IV complications, postoperative mortality, hospital stay, R0 resection, and operative time between younger and older patients undergoing laparoscopic hepatectomy [29]. Moreover, the minimal invasive approach in HCC cirrhotic patients has also the potential to reduce risk of post-operative liver decompensation and morbidities [30,31]. However, most of the studied patients were evaluated based on chronological age, comorbidities, and physical function -not on the comprehensive geriatric assessment.…”
Section: Liver Surgery In Older Patients With Hccmentioning
confidence: 99%
“…Thanks to improvements in radiological staging, anesthesia, surgical technique (understanding of segmental liver anatomy, parenchymal preserving surgery, bleeding control), and perioperative care it was possible to offer complex liver surgery to older patients. This is particularly important because, more than 60% of patients with primary and secondary liver tumors are older than 65 years at the moment of diagnosis [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation